OPTIMASI KONDISI PROSES EKSTRAKSI MINYAK BIJI PEPAYA - Yuniwati, Murni; Purwanti, Ani (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2008)
The papaya (Carica papaya L.) is a member of the small class dycotyledoneae, family caricaceae, and genus cariaca. This plant is native to the Central America and West Indies. It grows well at the tropical region with elevation 600-700 m above the sea level. Today papaya seed is only throwed away as a waste product, whereas in fact the papaya seed contains fatty acids with higher economic value which is called papaya oil. Oil of papaya seed can be obtained from solid - liquid extraction method. In this investiga-tion, the extraction of papaya seed was carried out in the stirred reactor with ethanol as a solvent. Solvent-extracted oil was distilled to separate papaya seed oil from solvent. The variables of investigation were extraction temperature, stirring speed, ratio between sol-vent volume and mass of papaya seed, and size of papaya seed. The extracted oil was a-nalyzed by using gas chromatography to determine the fatty acid composition. The opti-mum condition of papaya seed extraction were obtained at extraction temperature 300C, stirring speed 397 rpm, ratio between solvent volume and mass of papaya seed at 25 : 1, and size of papaya seed (-14/+20) mesh or average diameter 0.08 cm. The correlation between mass transfer coefficient and these variables is shown in the dimensionless e-quation below : Sh = 8,89 (10)5 Re(0,7785). Sc 0,9411.With the average error is 0.9706%.